The Chemosensory Transcriptome of a Diving Beetle - Montagné, Nicolas; Jager, Muriel; Chertemps, Thomas; Persyn, Emma; Jaszczyszyn, Yan; Meslin, Camille; Jacquin-Joly, Emmanuelle; Manuel, Michaël (Frontiers in Ecology and Evolution, 2021)
Insects astoundingly dominate Earth’s land ecosystems and have a huge impact on human life. Almost every aspect of their life relies upon their highly efficient and adaptable chemosensory system. In the air, most chemical signals that are detected at long range are hydrophobic molecules, which insects detect using proteins encoded by multigenic families that emerged following land colonization by insect ancestors, namely the odorant-binding proteins (OBPs) and the odorant receptors (ORs). However, land-to-freshwater transitions occurred in many lineages within the insect tree of life. Whether chemosensory gene repertoires of aquatic insects remained essentially unchanged or underwent more or less drastic modifications to cope with physico-chemical constraints associated with life underwater remains virtually unknown. To address this issue, we sequenced and analyzed the transcriptome of chemosensory organs of the diving beetle Rhantus suturalis (Coleoptera, Dytiscidae). A reference transcriptome was assembled de novo using reads from five RNA-seq libraries (male and female antennae, male and female palps, and wing muscle). It contained 47,570 non-redundant unigenes encoding proteins of more than 50 amino acids. Within this reference transcriptome, we annotated sequences coding 53 OBPs, 48 ORs, 73 gustatory receptors (GRs), and 53 ionotropic receptors (IRs). Phylogenetic analyses notably revealed a large OBP gene expansion (35 paralogs in R. suturalis) as well as a more modest OR gene expansion (9 paralogs in R. suturalis) that may be specific to diving beetles. Interestingly, these duplicated genes tend to be expressed in palps rather than in antennae, suggesting a possible adaptation with respect to the land-to-water transition. This work provides a strong basis for further evolutionary and functional studies that will elucidate how insect chemosensory systems adapted to life underwater.